How do gastropods grow synchronized shell sculpture? Effect of experimental varix manipulations on shell growth by Ceratostoma foliatum (Muricidae: Ocenebrinae). Issue 1 (4th March 2019) - Webster, Nicole; Richard Palmer, A.
Abstract: Gastropod shells display striking patterns in both color and sculpture, but rather little is known about the developmental mechanisms that produce those patterns. Here, we tested a physical feedback hypothesis for how snails control spatial patterning of shell sculpture. Varices—a form of synchronized, blade‐like axial sculpture—are produced at regular intervals around the shell and often aligned closely between adjacent whorls. Older varices were believed to provide a spatial cue about where to position a new varix. To test this hypothesis, we manipulated physical cues by cutting off varices or attaching new ones to the body whorl of individuals of Ceratostoma foliatum, and then allowing snails to grow a new varix. We found that previous varices on the shell were neither necessary nor sufficient to induce a new varix at a particular location. However, the position of older varices did appear to affect the fine tuning of subsequent varix placement. The results of our experiments therefore suggest that varix synchrony arises mainly from some internal mechanism that yields a standardized amount of spiral growth per growth spurt. We also found that shell damage can induce varix production in unusual or aberrant locations during subsequent shell growth.